Angiotensin II Type 1 Receptor rs5186 Gene Variant Predicts Incident NAFLD and Associated Hypertension: Role of Dietary Fat-Induced Pro-Inflammatory Cell Activation. (April 2019) - Musso, Giovanni; Saba, Francesca; Cassader, Maurizio; Paschetta, Elena; De Michieli, Franco; Pinach, Silvia; Framarin, Luciana; Berrutti, Mara; Leone, Nicola; Parente, Renato; Ayoubi Khajekini, Mohammad Taghi; Zarovska, Adriana; et al.
Abstract : OBJECTIVES: Hypertension has been linked to the presence and severity of nonalcoholic fatty liver disease (NAFLD) through unclear mechanisms. The gain-of-function rs5186 A1166C variant in angtiotensin receptor type 1 (AGTR1) gene has been linked to hypertension, cardiovascular disease and metabolic syndrome. We assessed the impact of AGTR1 A1166C variant on NAFLD incidence and severity and on glucose and lipid metabolism and explored the underlying mechanisms. METHODS: We followed up 314 healthy nonobese, nondiabetic, nonhypertensive, insulin-sensitive participants in a population-based study, characterized for AGTR1 rs5186 A1166C variant, adipokine profile, inflammatory and endothelial dysfunction markers. An independent cohort of 78 biopsy-proven nondiabetic NAFLD patients and controls underwent an oral glucose tolerance test with Minimal Model analysis of glucose homeostasis, and an oral fat tolerance test with measurement of plasma lipoproteins, adipokines, MCP-1, calprotectin, and nuclear factor-κB activation in circulating mononuclear cells. RESULTS: AGTR1 A1166C polymorphism predicted 9.8-year incident NAFLD (odds ratio: 1.67, 95% CI: 1.26–2.21) and hypertension (odds ratio: 1.49, 95% CI: 1.12–2.63) and 9-year increase in cardiovascular disease risk and endothelial dysfunction markers. In the cross-sectional cohort, AGTR1 C allele carriers had higher insulin resistance. Despite comparable fasting lipid profiles, AGTR1 C allele carriers showed postprandial triglyceride-rich and cholesterol-rich VLDL lipoprotein accumulation, higher resistin, MCP-1 and calprotectin responses and nuclear factor-κB activation in mononuclear cells, and a blunted postprandial adiponectin response to fat, which predicted liver histology, hepatocyte apoptosis activation, insulin resistance, and endothelial dysfunction. DISCUSSION: AGTR1 A1166C variant affects liver disease, insulin resistance, and endothelial dysfunction in NAFLD, at least in part by modulating adipokine, chemokine, and pro-inflammatory cell activation in response to fat ingestion.